Mastering CentOS 7 Linux server : configure, manage, and secure a CentOS 7 Linux server to serve a variety of services provided in a sustainable computer's infrastructure /: configure, manage, and secure a CentOS 7 Linux server to serve a variety of services provided in a sustainable computer's infrastructure. (2016) - Alibi, Mohamed; Roy, Bhaskarjyoti
No abstract available